Circulating Tumor DNA in Head and Neck Squamous Cell Carcinoma - Brandt, Anna; Thiele, Benjamin; Schultheiß, Christoph; Daetwyler, Eveline; Binder, Mascha (Cancers, 2023)
Tumors shed cell-free DNA (cfDNA) into the plasma. “Liquid biopsies” are a diagnostic test to analyze cfDNA in order to detect minimal residual cancer, profile the genomic tumor landscape, and monitor cancers non-invasively over time. This technique may be useful in patients with head and neck squamous cell carcinoma (HNSCC) due to genetic tumor heterogeneity and limitations in imaging sensitivity. However, there are technical challenges that need to be overcome for the widespread use of liquid biopsy in the clinical management of these patients. In this review, we discuss our current understanding of HNSCC genetics and the role of cfDNA genomic analyses as an emerging precision diagnostic tool.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cell-free DNA (cfDNA); head and neck squamous cell carcinoma (HNSCC); liquid biopsy; monitoring; prognostication; resistance